REVERTING OR PROGRESSING: THE DILLEMA OF HIGHER EDUCATION ENGLISH INSTRUCTION IN A HETEREGENOUS CLASSROOM - Wiramarta, Kadek; Paragae, I Gusti Ayu Putu Novita Sari (International Journal of Instructions and Language Studies, 2024)
It is common for university classes to be heterogeneous due to the vast range of students' backgrounds. Undoubtedly, teachers employ their own strategies to address this matter. Hence, this study aims to investigate how teachers design the teaching approach and learning resources in the presence of a heterogeneous classroom. This study used Interpretative Phenomenological Analysis (IPA) to investigate the approach employed by English lecturers in universities when managing diverse classrooms. A total of six participants were interviewed in order to obtain the desired data. These data were subsequently evaluated thematically to investigate the narrative of university lecturers in higher education regarding this issue. The results of this study revealed that every participant had actively sought to acquire knowledge regarding the extent of student diversity present in the classroom. Participants also devised effective strategies for constructing the learning material and teaching methods that will optimize the development of all students' capacity. While there might be varying opinions among participants, they unanimously acknowledged that effectively teaching a diverse classroom requires careful thought and consideration in order to meet the individual needs of all students, regardless of students varying level of knowledge. This study hopefully can elucidate some teaching strategies while dealing with heterogeneous classroom.